On the electrochemical behaviour of V-N-8Cr weathering steel in simulated industrial atmosphere. (17th February 2020) - Liu, Yue; Wu, Hong-Yan; Du, Lin-Xiu; Misra, R. D. K.
ABSTRACT: We have studied here the wet/dry cyclic corrosion behaviour of V-N-0.8Cr weathering steel and compared with a reference steel (Q345B) in 0.01 mol/L NaHSO3 simulated industrial atmosphere. The study indicated that the coherent protective oxide layer formed in the surface of V-N-0.8Cr microalloyed weathering steel, contained corrosion resistant alloying elements (Cr, Ni, Cu, P, Mo). The addition of Cr significantly inhibited the corrosion of weathering steel. The corrosion rate of V-N-0.8Cr and Q345B steel after 360 h corrosion were 1.60 g/(h·cm 2 ) and 2.42 g/(h·cm 2 ) respectively. The major corrosion products in both the steels mainly constituted of α-FeOOH and γ- FeOOH and Fe3 O4 . The stratification of the corrosion layer evolved into a dual-layer structure, where the outer layer was dense and the inner layer was a loose and porous structure in V-N-0.8Cr weathering steel. This is different from previous studies. Cr tends to be concentrated in the inner corrosion layer.